Measuring Differential Volume Using the Subtraction Tool for Three-Dimensional Breast Volumetry: A Proof of Concept Study. (December 2020) - Jeon, Faith Hyun Kyung; Griffin, Michelle; Almadori, Aurora; Varghese, Jajini; Bogan, Stephanie; Younis, Ibby; Mosahebi, Ash; Butler, Peter E.
Background. Three-dimensional (3D) photography provides a promising means of breast volumetry. Sources of error using a single-captured surface to calculate breast volume include inaccurate designation of breast boundaries and prediction of the invisible chest wall generated by computer software. An alternative approach is to measure differential volume using subtraction of 2 captured surfaces. Objectives. To explore 3D breast volumetry using the subtraction of superimposed images to calculate differential volume. To assess optimal patient positioning for accurate volumetric assessment. Methods. Known volumes of breast enhancers simulated volumetric changes to the breast (n = 12). 3D photographs were taken (3dMDtorso) with the subject positioned upright at 90° and posteriorly inclined at 30°. Patient position, breathing, distance and camera calibration were standardised. Volumetric analysis was performed using 3dMDvultus software. Results. A statistically significant difference was found between actual volume and measured volumes with subjects positioned at 90° ( P < .05). No statistical difference was found at 30° ( P = .078), but subsequent Bland–Altman analysis showed evidence of proportional bias ( P < .05). There was good correlation between measured and actual volumes in both positions (r = .77 and r = .85, respectively). Univariate analyses showed breast enhancer volumes of 195 mL and 295 mL to incur bias. The coefficient of variation was 5.76% for single observer analysis. Conclusion. Positioning the subject at a 30° posterior incline provides more accurate results from better exposure of the inferior breast. The subtraction tool is a novel method of measuring differential volume. Future studies should explore methodology for application into the clinical setting.